2020
DOI: 10.3390/app10248962
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage in Propane-Hydrate: Theoretical and Experimental Study

Abstract: There have been studies on gas-phase promoter facilitation of H2-containing clathrates. In the present study, non-equilibrium molecular dynamics (NEMD) simulations were conducted to analyse hydrogen release and uptake from/into propane planar clathrate surfaces at 180–273 K. The kinetics of the formation of propane hydrate as the host for hydrogen as well as hydrogen uptake into this framework was investigated experimentally using a fixed-bed reactor. The experimental hydrogen storage capacity propane hydrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…They were able to produce hydrate at pressures ranging from 2.51 to 7.9 MPa and at corresponding temperatures equal to 275.3-283.2 K. In this work, as in similar studies, the concentration of hydrogen within the hydrate lattice was the most limiting factor. In addition, recent studies confirm the advantages, in terms of reduced pressures required, associated with the enclathration of hydrogen mixed with natural gas mixtures [88][89][90].…”
Section: Gas Hydrate As a Promising Solution For Hydrogen Storagementioning
confidence: 78%
“…They were able to produce hydrate at pressures ranging from 2.51 to 7.9 MPa and at corresponding temperatures equal to 275.3-283.2 K. In this work, as in similar studies, the concentration of hydrogen within the hydrate lattice was the most limiting factor. In addition, recent studies confirm the advantages, in terms of reduced pressures required, associated with the enclathration of hydrogen mixed with natural gas mixtures [88][89][90].…”
Section: Gas Hydrate As a Promising Solution For Hydrogen Storagementioning
confidence: 78%
“…H2 storage capacity (wt.%) can be reduced by increasing the molecular weight of the promoter [337]. NEMD simulations to study the H2 storage in C3H8 hydrate revealed that the diffusion coefficient at 273 K is approximately 1.5 times higher than that at 260 K. Based on the experimental and theoretical estimations, H2 content in C3H8 hydrate can be stored by 1.04 wt% and 1.13 wt% respectively [338]. It was estimated that for the pressure ranges over 270 MPa, double occupancy prevails with the single occupancy of Argon molecules in large cages [339].…”
Section: Hydrate Cage Occupancy and Storage Capacitymentioning
confidence: 99%
“…Their computations also illustrated that a single H2 molecule occupies the small cages of the hydrate, whereas the large cages are likely to contain one THF molecule together with one H2 molecule. Ghaani et al [232] utilized non-equilibrium molecular dynamics (NEMD) simulations to analyze H2 release and uptake from propane planar clathrate surfaces at 180-273 K. The obtained experimental H2 storage capacity (using a fixed bed reactor) was 1.04 wt.% in comparison to the theoretically obtained 1.13 wt.% of the propane hydrate. A novel dual-function (thermodynamic and kinetic) promoter, 1,3dioxolane (DIOX), was proposed by Zhang et al [233] for H2-bearing sII hydrate formation.…”
Section: Hydrogen Storage In Clathratesmentioning
confidence: 99%